The Writing Culture of Ancient Dadān A Description and Quantitative Analysis of Linguistic Variation - Kootstra, Fokelien (Brill, 2022)
This work focuses the social context of writing in ancient Western Arabia in the oasis of ancient Dadan, modern-day al-ʿUlā in the northwest of the Arabian Peninsula between the sixth to first centuries BC. It offers a description and analysis of the language of the inscriptions and the variation attested within them. It is the first work to perform a systematic study of the linguistic variation of the Dadanitic inscriptions. It combines a thorough description of the language of the inscriptions with a statistical analysis of the distribution of variation across different textual genres and manners of inscribing. By considering correlations between language-internal and extralinguistic features this analysis aims to take a more holistic approach to the epigraphic object. Through this approach an image of a rich writing culture emerges, in which we can see innovation as well as the deliberate use of archaic linguistic features in more formal text types.